ADUBAÇÃO MINERAL E BIOESTIMULANTES EM PASTAGENS DEGRADADAS NO BIOMA MATA ATLÂNTICA - Castro, Andre Soares de (2022)
Soil degradation is an aggravating factor throughout the country, which is subject to the event for several reasons, such as poor soil management, poor phytotechnical management of plants, including livestock management, in addition to the relief, which many of the are accentuated and also climatic factors. Thus, soil degradation has been highlighted in the livestock sector as one of the main aggravating factors of low productivity, which suffers daily from a reduction in forage yield, which directly advocates the yield of Brazilian herds and the production costs of this activity. Given the above, the present work aimed to recover the productive capacity of pastures in areas with conditions of high level of degradation subjected to the use of biostimulants in two tropical forage species and on two perspectives of soil management systems (with scarification - SCE and without scarification – SSE). Thus, the use of scarification (SCE), associated with biological inputs, and the reduction of mineral fertilization provided better technical characteristics and green and dry biomass for forage plants Urochloa cv. Marandu and Stylosanthes cv. Campo Grande I and II. It is also noteworthy that the use of scarification (SCE) provided better results in the distribution and amount of root biomass and physiological characteristics, in addition to presenting lower soil compaction results in relation to the system without scarification (SSE). It is noteworthy that, in both forages, the use of biotechnologies associated with SCE, and with reduced doses of mineral fertilizer, showed values similar to the use of 100% mineral fertilizer (treatment 2). Thus, the use of biostimulants for regions with sloping relief, low rainfall, little technology and low availability of nutrients, can be an alternative in the initial recovery of areas with a high level of degradation.